Regulation studies of phaC(C1 and C2) genes in Pseudomonas sp. USM 4-55 - Hasan, Kamariah; Najimudin, Mohd Nazalan; Samian, Mohd Razip (Penerbit Universiti Sains Malaysia, 2004)
Among the various biodegradable plastics available, polyhydroxyalkanoates (PHAs) attract a lot of attention because these polymers are produced by bacteria and have thermoplastic properties. They are biodegradable, biocompatible, moisture resistant, versatile, have long shelf life and are made from renewable source materials (Pouton et al., 1996).